Le marché et l’organisation du travail : 1965-1995 et le monde de demain - Lacroix, Robert (Assurances)

(untitled) (HEC Montréal, 1996)
A company's success depends on its manpower and organization. We thank Professor Robert Lacroix for authorizing us to print the speech he presented on October 5th at a seminar entitled "At the dawn of the 21st century" which was jointly organized by Cirano and MLH + A inc. The author reviews the '60s, the glorious years, and the major changes that have affected the job market and work organization. In his conclusion, he ponders the future in the context of the global economy and touches on some key questions: the permanence of work, ongoing training, methods of compensation and employee benefits.